2006
DOI: 10.1897/05-299r.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic toxicity of silver to the sea urchin (Arbacia punctulata)

Abstract: The chronic toxicity of silver to the sea urchin (Arbacia punctulata) was determined in 30 per thousand salinity seawater during a three-part study: A fertilization test (1-h sperm exposure), a 48-h embryo test, and a 30-d adult test. Combined data from the three tests resulted in a lowest-observed-effect concentration of 19 microg/L, a no-observed-effect concentration of 8.6 microg/L, and a maximum acceptable toxicant concentration of 13 microg/L, based on measured concentrations of dissolved silver. The 96-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…Presumably, our observations are related to differences in the physical and chemical properties of Ag in aqueous and nanoparticulate forms and kinetic constraints on the partial conversion of the latter to the former. The concentration at which aqueous Ag is measurably toxic in the marine environment, evaluated using a variety of organisms and end-points, appears to be in the range \1 to about 15 lg l -1 (Luoma et al 1995;Bianchini et al 2005;Ward et al 2006), quantitatively consistent with observations made in the present study. Since Ag does not appear to form particularly strong complexes with organic ligands in sea water (Miller and Bruland 1995), its aqueous speciation is dominated by various chloro-complexes (see Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Presumably, our observations are related to differences in the physical and chemical properties of Ag in aqueous and nanoparticulate forms and kinetic constraints on the partial conversion of the latter to the former. The concentration at which aqueous Ag is measurably toxic in the marine environment, evaluated using a variety of organisms and end-points, appears to be in the range \1 to about 15 lg l -1 (Luoma et al 1995;Bianchini et al 2005;Ward et al 2006), quantitatively consistent with observations made in the present study. Since Ag does not appear to form particularly strong complexes with organic ligands in sea water (Miller and Bruland 1995), its aqueous speciation is dominated by various chloro-complexes (see Table 1).…”
Section: Discussionsupporting
confidence: 89%
“…Previously, Dupont and Ahner (2005) have shown that phytoplankton exude strong metal ligands, which were small peptides containing thiols from cysteine residues when under metal challenge. Ward et al (2006) showed a similar pattern of decreasing Ag ? resulting from exudates for sea urchins when confronted with increasing silver challenges.…”
Section: Fish Studiesmentioning
confidence: 68%
“…Ag-CRS complexation and the overall bioavailability of the Ag ? that contributes to toxicity may be affected by several factors in a defined test chamber including: the rate of dosing, the number (surface area and weight) of organisms, the particular organism (e.g., fish vs. invertebrates), the presence of food and food type (present study; Ward et al 2006), and the nutritional impact of the food to the organism. Use of an experimental design that addresses these factors in a consistent manner is necessary to achieve an improved characterization of the toxicity of silver, and possibly other metals, to different organisms over a range of exposure scenarios.…”
Section: Acr Determinationmentioning
confidence: 99%
“…When metals concentrations are sufficiently elevated, from either anthropogenic or natural sources, selection for metals-resistant populations can occur, resulting in inheritable genetic adaptations by animals (Vidal and Horne 2003a, b;Zaldibar et al 2006), plants (Deng et al 2007), and bacteria (Jin et al 2007). In some cases reduced metals uptake (Hansen et al 2006) or accumulation and detoxification mechanisms may be sufficient to deal with metal influxes without selection for a metal-tolerant population (Zhou et al 2003), for instance regulation of metals via mucus production by snails (Notten et al 2006), biofilm production by algae (García-Menza et al 2005), or exudation of strong thiol ligands into seawater (Ward et al 2006). In other cases detoxification may be insufficient to avoid toxicity (Giguère et al 2006).…”
Section: Tolerancementioning
confidence: 99%